2018
DOI: 10.1016/j.cell.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of piRNA Binding Sites Reveals the Argonaute Regulatory Landscape of the C. elegans Germline

Abstract: piRNAs (Piwi-interacting small RNAs) engage Piwi Argonautes to silence transposons and promote fertility in animal germlines. Genetic and computational studies have suggested that C. elegans piRNAs tolerate mismatched pairing and in principle could target every transcript. Here we employ in vivo cross-linking to identify transcriptome-wide interactions between piRNAs and target RNAs. We show that piRNAs engage all germline mRNAs and that piRNA binding follows microRNA-like pairing rules. Targeting correlates b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
191
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(196 citation statements)
references
References 70 publications
3
191
1
1
Order By: Relevance
“…This process is involved in the recognition of expressed (self ) transcripts through transgenerational CSR-1 memory, versus silenced transcripts/foreign sequences (non-self ), in the germline across generations. Recent studies analyzing the rules of piRNA base pairing with mRNAs confirmed the requirement in C. elegans of strong complementarity in the seed region (nucleotides 2-8) followed by an additional match at nucleotides 14-19 (Shen et al, 2018;Zhang et al, 2018).…”
Section: The Conservation Of Endogenous Mrna Regulation By Pirnasmentioning
confidence: 87%
“…This process is involved in the recognition of expressed (self ) transcripts through transgenerational CSR-1 memory, versus silenced transcripts/foreign sequences (non-self ), in the germline across generations. Recent studies analyzing the rules of piRNA base pairing with mRNAs confirmed the requirement in C. elegans of strong complementarity in the seed region (nucleotides 2-8) followed by an additional match at nucleotides 14-19 (Shen et al, 2018;Zhang et al, 2018).…”
Section: The Conservation Of Endogenous Mrna Regulation By Pirnasmentioning
confidence: 87%
“…To assess targeting requirements for tapiR1, we introduced mismatches in the piRNA target sites. Three consecutive mismatches were tolerated unless they were located in the t1 to t9 region of the piRNA (the nucleotides based-paired to piRNA positions 1 to 9) (Fig 2C, Extended Data Fig 6A), and single mismatches only impaired silencing at positions t3 to t7 (Extended data Fig 6A,B), reminiscent of a microRNA seed 35 and comparable to what has been termed the piRNA seed in C. elegans 36,37 . Even though tapiR1 targeting requirements resemble those of miRNAs, the results are unlikely to be due to the piRNA being funnelled into the miRNA pathway.…”
Section: Mainmentioning
confidence: 99%
“…Because auxin can be washed away, the system is also potentially reversible, although restoration to full protein levels may require a lengthy recovery. Like the methods described above, AID can degrade proteins rapidly and has been used to study the loss-of-function phenotype of several different types of proteins (Zhang et al 2015(Zhang et al , 2018bKerk et al 2017;Pelisch et al 2017;Liu et al 2017a;Patel and Hobert 2017;Yu et al 2017;Shen et al 2018;Ferrandiz et al 2018;Kasimatis et al 2018;Serrano-Saiz et al 2018). One potential issue is that addition of the AID degron tag has been reported in a few cases to interfere with function or stability of the tagged protein even in the absence of TIR1 and auxin (Kerk et al 2017;Patel and Hobert 2017;Schmidt et al 2017).…”
Section: Experimental Considerationsmentioning
confidence: 99%